Forceful thermopneumatic actuator for miniaturized valve - Tan, Adrian Wei Yee (2014)
This dissertation presents design, development and a forceful thermopneumatic actuator for miniaturized valves. Valves are devices used regulate, direct or control the flow in fluidic systems. They are sized according to the needed fluid flow rate and pressure. Large valves control large fluid flow rate with high pressure while miniature valves only able control for lower fluid flow rate and pressure. In comparison to large valves, miniature valves are weak. However, miniature valves are important for precision control over flow rate, able to fit in extremely compact fluidic system, low power consumption and very fast response time. Miniaturized valves are widely used in medical equipment where fluidic control is very important, for example dialysis machine, portable oxygen concentrator and automated pill